Competitive Frontiers: Women In Management And The Performance Of Microfinance Banks In South-East Nigeria - Joy, Nonyelum Ugwu; Ndubuisi, Peter Ositadinma; Ogbaekirigwe, Charles (Archives of Business Research, 2018)
This study focused on Competitive Frontiers: Women in Management. The study took a descriptive survey approach and covered a sample size of 64 members of senior staff randomly selected from Ecobank and First Bank Nig. Plc within the South-Eastern part of Nigeria. A five point likert scale questionnaire was used to collect data and the data collected was analyzed using inferential statistics. The hypotheses were tested using Mann-Whitney Test (U) using the 20.0 version of statistical package for social sciences (SPSS). From the result of the SPSS output for hypotheses 1 and 2, their respective p-values were lesser than the level of significance (i.e 0.000 and 0.04<0.05 respectively), this led to the rejection of the two null hypotheses tested in this work. The study therefore recommends that banks should deploy more women in the management of their marketing activities in order to enhance their marketing performance which has a direct link to their competitiveness